Evaluation of validity of digital photograph based dietary intake in school children - Orkun Erkılıç, Tuğçe; Pekcan, Ayla Gulden (Progress in Nutrition, 2020)
Study Objectives: Accurately assessing children’s dietary intake is a challenging task. This study aimed to assess the dietary intake of school children using 24 hour records (RM) and digital photograph (DM) based dietary intake methods, to validate the use of a novel digital image-based food record and to assess the feasibility. Methods: This study was held in Mehmet Özcan Torunoğlu Elementary School in Ankara on 40 (50.0% boys) children. A questionnaire was applied, general characteristics, food consumption frequencies and physical activity levels of the children were assessed. Each week 5 children were recruited and 24-h record method (RM) was applied for 4 consecutive days with one day as a weekend day. For the same period by using a digital camera, the participants were instructed and demonstrated to take digital photos (DM) for all meals and snacks, before and after the consumption of foods. Anthropometric measurements (height, body weight, waist, and hip circumferences) of children were taken and body mass index (BMI), waist circumference/height ratios were calculated. Results: Mean (±SD) age of the boys and girls were 8.05±0.22 and 8.1±0.31 years, respectively. According to RM and DM, daily energy intakes of boys were 2226.9 ±613.13 and 1611±209.79 kcal (p